AJARAN PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM KEBIJAKAN HUKUM PIDANA DI BIDANG MAYANTARA - Laila Mulasari (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
Imposition of a basic responsibility of corporations in a law (in this case specifically related to criminal law policy in areas mayantara) is a combination from several existed teaching / doctrine of criminal liability. Moreover, by looking at trends and developments in criminal law including the Criminal Law of Indonesia, which was recently accepted the establishment that corporation, though in its heart has no criminal liability but can be burdened also. Proved that the burden of criminal responsibility, especially if the perpetrators of criminal acts were the corporation itself, is still charged either to the corporation and the managers that have a functional position in the corporate organizational structure.